Penguatan Kapasitas SDM Logistik Berbasis Artificial Intelligence dan Internet of Things pada Jasa Pengiriman Barang di Bandara Soekarno-Hatta - Astri Rumondang Banjarnahor; Juliater Simarmata; Imam Ozali; Sinung Tri Nugroho; Agus Nugroho (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This community service study was motivated by the low digital literacy of logistics human resources, frequent address errors, inefficient sorting processes, and weak operational monitoring in freight delivery services at Soekarno-Hatta Airport. The study aimed to improve the capacity of logistics personnel in utilizing Artificial Intelligence (AI) and Internet of Things (IoT) technologies to support faster, more accurate, and data-driven distribution services. The method used was a participatory capacity-building approach consisting of five stages: needs assessment, module development, training implementation, intensive mentoring, and sustainability evaluation. The program involved logistics personnel through interactive learning, practical simulations, case-based discussions, and continuous technical assistance to ensure effective technology adoption in daily operations. The results emphasized substantial improvements in digital system understanding from 40% to 88%, data management skills from 35% to 85%, and confidence in using technology from 45% to 90%. Operational performance also improved, as address errors decreased from 15% to 6%, reattempts from 18% to 8%, sorting speed increased by 30%, and on-time delivery rose from 78% to 92%. Thus, this training model can be replicated sustainably in similar logistics sectors.